Modifying Uno Cards as Learning Media for Enhancing Numeracy Skills of Elementary Students in Whole Number Topic (Edumatika : Jurnal Riset Pendidikan Matematika, 2025)
Numeracy is a fundamental competence that supports students’ ability to apply mathematical concepts in everyday situations. However, many elementary school students still face difficulties in understanding whole number concepts, which are essential for developing higher-order numeracy. This study aims to develop and validate a modified Uno card game called Party Math as a learning media to enhance students’ numeracy skills in the topic of whole numbers. The research employed a Research and Development (R&D) approach adapted from the ADDIE model, consisting of the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through expert validation questionnaires, student response questionnaires, and pre-test and post-test results. The data were analyzed using descriptive and quantitative techniques. The results show that the modified Uno card game meets the criteria of validity, practicality, and effectiveness. Expert evaluations from subject matter specialists, media experts, and teachers indicated that the media is highly suitable for classroom use. Student responses also revealed that the game is engaging, easy to play, and helps them understand whole number operations. Therefore, the Party Math card game can be recommended as an effective and enjoyable tool to strengthen numeracy learning in elementary schools.